Colored microcrystalline glass and preparation method thereof
By melting a variety of different color glass compositions into a variety of glass liquids of different colors, and controlling temperature differences in the process of molding and thermal treatment, the color glass in the existing technology cannot achieve controlling the color of different regions. Realize the diverse color and good strength of color micro -crystal glass.
Patent Information
- Application Number
- CN202410409557.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-07
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-04-07
AI Technical Summary
The prior art cannot achieve controllable color of color of colored glass in different areas, resulting in monotonous glass color and difficult to meet market demand.
By melting a variety of different color glass compositions into a variety of different color glass fluids, and controlling the temperature difference during the molding process, ensure that color substrate glass will not appear in the process of molding and thermal treatment. The color of different regions of the glass is controllable.
The color of different areas of color glass is controlled, ensuring the uniform strengthening of color micro -crystal glass and good strength performance, and meet the market's demand for diverse colors.
Smart Images

Figure CN119371106A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of microcrystalline glass, and in particular to colored microcrystalline glass for electronic device housings, and specifically to a colored microcrystalline glass and a preparation method thereof. Background Art
[0002] Back panel glass refers to the glass back cover of the mobile phone. Traditional back panels are mainly made of metal and plastic. With the development and application of 5G and wireless charging technology, the shielding effect of metal back panels on signals has become more and more prominent. Therefore, the back panels are gradually replaced by non-metallic materials, and glass and microcrystalline glass will become the main alternative materials due to their excellent performance. With the widespread popularity of smart phones, consumers' requirements for mobile phones are no longer limited to performance and lifespan. The personalized requirements for visual effects and appearance are also getting higher and higher. The back panel does not have to have excellent transmittance like the front cover, and it can be personalized in appearance. Therefore, the color selection and design of the back cover of colored glass or microcrystalline glass mobile phones has become a hot topic for terminal mobile phone manufacturers.
[0003] At present, the color design of mobile phone back covers mainly adopts film pasting, electroplating and spray painting. Both processes are post-processing on the transparent glass cover. The color has developed from the initial single color to the popular gradient color and regional color. The diversified colors meet the pursuit of fashion by different consumers; the discoloration and cheap texture of film pasting and electroplating and spray painting have also made terminal mobile phone manufacturers gradually focus from the development of film color to the glass body, in order to achieve a three-dimensional, transparent and saturated color effect through the color of the glass body.
[0004] The prior art has conducted some research on the process of preparing colored glass, which usually involves adding different colorants to glass components to obtain colored glass of different colors. However, the colored glass obtained in this way often has only one color, which makes the color of the glass itself very monotonous and difficult to meet market demand. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a colored micro-ceramic glass to achieve coloring of colored glass in different areas, so as to solve the technical problem that colored glass in the prior art cannot achieve controllable colors in different areas.
[0006] In order to solve the above technical problems, in the first aspect, the present application provides a colored microcrystalline glass, which is obtained by heat treating a colored substrate glass; the colored substrate glass comprises a plurality of different colored glass compositions melted into a plurality of different colored glass liquids and simultaneously molded into one, and the colored substrate glass has different color regions.
[0007] In some embodiments, a plurality of glass compositions of different colors are melted into glass liquids of different colors and, when formed, the following conditions are met: the absolute value of the temperature difference between the glass liquids of different colors when the viscosity is 300P is less than or equal to 30°C, and the absolute value of the temperature difference when the viscosity is 600P is less than or equal to 40°C; this ensures that the colored substrate glass will not have defects such as breakage, flaws, cracks, etc. during the forming process and can be formed intactly.
[0008] In some embodiments, when the glass compositions of different colors are heat-treated after being formed, the absolute value of the temperature difference between the nucleation temperatures of the glass compositions of different colors is less than or equal to 20°C.
[0009] In some embodiments, when the glass compositions of different colors are heat-treated after being formed, the absolute value of the temperature difference between the crystallization temperatures of the glass compositions of different colors is less than or equal to 20°C.
[0010] In some embodiments, after the glass compositions of different colors are formed and heat treated, the absolute value of the difference between the average thermal expansion coefficients of the glass compositions of different colors is less than or equal to 0.8×10 -6 / K; It can achieve uniform strengthening of colored microcrystalline glass and has good strength performance.
[0011] In some embodiments, the glass compositions of various colors include the following components, measured in mole percentage of oxides:
[0012] SiO 2 : 66~71%;
[0013] Al 2 O 3 : 3.5~5.0%;
[0014] Na 2 O: 0-5.0%, not 0;
[0015] Li 2 O: 18-23%;
[0016] P 2 O 5 : 0.5~1.5%;
[0017] ZrO 2 : 1.5~4.0%;
[0018] At least one colorant, the colorant is Au, Ag, Cr 2 O 3 , transition metal oxides, and at least one of rare earth metal oxides.
[0019] In some embodiments, the glass compositions of various colors further include the following components, measured in mole percentage of oxides:
[0020] K 2 O: 0~0.5%;
[0021] CaO: 0-1.5%;
[0022] B 2 O 3 :0~2%.
[0023] In some embodiments, the number of glass compositions of different colors is 2 or more, or 3 or more.
[0024] In some embodiments, the compositions of the glass compositions of different colors differ partially or entirely in components other than the colorant and in their contents.
[0025] In some embodiments, the colored substrate glass is formed by at least one of casting, calendering, overflow, float, and narrow-slit drawdown.
[0026] In some embodiments, glass liquids of multiple different colors are molded into one piece in different regions.
[0027] In some embodiments, the plurality of glass compositions of different colors have the same primary crystalline phase after each forming and heat treatment.
[0028] In some embodiments, the main crystalline phase of the glass compositions of different colors after each molding and heat treatment is a lithium-containing crystalline phase, including at least one of petalite, lithium monosilicate, lithium disilicate, and eucryptite.
[0029] In some embodiments, the thermal treatment includes a nucleation treatment and a crystallization treatment.
[0030] In some embodiments, the nucleation treatment is to heat the colored substrate glass from room temperature to a nucleation temperature at a heating rate of 1 to 10° C. / min.
[0031] In some embodiments, the temperature of the nucleation treatment is 500-600° C., and the time of the nucleation treatment is 180-300 min.
[0032] In some embodiments, the crystallization treatment is to heat the colored substrate glass from a nucleation temperature to a crystallization temperature at a heating rate of 1 to 10° C. / min.
[0033] In some embodiments, the temperature of the crystallization treatment is 600-800° C., and the time of the crystallization treatment is 30-180 min.
[0034] In a second aspect, the present application provides a method for preparing the above-mentioned colored micro-ceramic glass, comprising the following steps:
[0035] Step 1: Mix components of glass compositions of various colors respectively, and then melt them to obtain glass liquids of various colors;
[0036] Step 2: forming the glass liquids of various colors obtained in step 1 into one body, and annealing the formed glass liquids to obtain colored substrate glass;
[0037] Step 3: Heat-treat the colored substrate glass obtained in step 2 to obtain colored microcrystalline glass.
[0038] In some embodiments, in step 1, the melting temperature is 1350-1650° C., and the melting time is 4-13 hours.
[0039] In some embodiments, in step 2, a plurality of glass liquids of different colors are molded into one body in different regions.
[0040] In some embodiments, in step 2, the molding method is at least one of casting molding, calendering molding, overflow molding, float molding, and narrow slit drawdown.
[0041] In some embodiments, in step 2, the annealing temperature is 450-500° C., and the annealing time is 12-48 hours.
[0042] In some embodiments, in step 3, the heat treatment includes a nucleation treatment and a crystallization treatment.
[0043] In some embodiments, the temperature of the nucleation treatment is 500-600° C., and the time of the nucleation treatment is 180-300 min.
[0044] In some embodiments, the temperature of the crystallization treatment is 600-800° C., and the time of the crystallization treatment is 30-180 min.
[0045] In some embodiments, the colored substrate glass is heated from room temperature to a nucleation temperature at a heating rate of 3 to 10° C. / min.
[0046] In some embodiments, the colored substrate glass is heated from the temperature of the nucleation process to the temperature of the crystallization process at a heating rate of 3 to 10° C. / min.
[0047] In a third aspect, the present application provides a strengthened colored microcrystalline glass, which is obtained by chemically strengthening the colored microcrystalline glass as described above or the colored microcrystalline glass prepared by the method for preparing the colored microcrystalline glass described above.
[0048] In some embodiments, chemical strengthening comprises single-step chemical strengthening or multi-step chemical strengthening.
[0049] In some embodiments, a single-step chemical strengthening step is performed using a mixture containing NaNO 3 A salt bath, preferably NaNO 3 The content is 30-100wt%.
[0050] In some embodiments, the temperature of the single-step chemical strengthening is 450-500°C.
[0051] In some embodiments, the time for single-step chemical strengthening is 1 to 15 hours.
[0052] In some embodiments, the multi-step chemical strengthening includes two steps of chemical strengthening, wherein the first step of chemical strengthening uses a 3 A salt bath, preferably NaNO 3 The content of KNO is 30-100wt%; the second step of chemical strengthening uses 3 A salt bath, preferably KNO 3 The content is 60-100wt%.
[0053] In some embodiments, the temperature of the first step chemical strengthening is 450-500° C., and the time of the first step chemical strengthening is 2-10 hours.
[0054] In some embodiments, the temperature of the second step chemical strengthening is 450-500° C., and the time of the second step chemical strengthening is 1-5 hours.
[0055] In some embodiments, at a thickness of 0.60 mm, the average single-rod static compressive strength of the strengthened colored glass-ceramics is greater than or equal to 300 N, preferably 320-450 N.
[0056] In some embodiments, at a thickness of 0.60 mm, the average drop resistance height of the strengthened colored microcrystalline glass is greater than or equal to 1.80 m, preferably 1.80-2.50 m.
[0057] In a fourth aspect, the present application provides an application of the colored microcrystalline glass as described above, or the colored microcrystalline glass prepared by the above-mentioned colored microcrystalline glass preparation method, or the above-mentioned colored strengthened microcrystalline glass in mobile phone back covers, electronic terminals, decorative parts, handicrafts, jewelry or portable digital devices.
[0058] In a fifth aspect, a consumer electronic product comprises: a housing comprising a front surface, a back surface and a side surface; electronic components at least partially located within the housing, the electronic components comprising at least a controller, a memory and a display, the display being located at the front surface of the housing or adjacent to the front surface of the housing; and a cover glass arranged on the display, wherein at least a portion of the housing comprises the colored microcrystalline glass as described above, or the colored microcrystalline glass prepared by the method for preparing the colored microcrystalline glass as described above, or the strengthened colored microcrystalline glass as described above.
[0059] In a sixth aspect, an electronic device comprises the colored microcrystalline glass as described above, or the colored microcrystalline glass prepared by the method for preparing the colored microcrystalline glass as described above, or the strengthened colored microcrystalline glass as described above.
[0060] Compared with the prior art, the present invention has the following beneficial effects:
[0061] 1. The present application uses a variety of glass compositions of different colors to melt into a variety of glass liquids of different colors and simultaneously mold them into one to obtain a colored substrate glass with different color areas, and then heat-treats it to obtain a colored microcrystalline glass; the colors of different areas of the colored glass can be controlled.
[0062] 2. The present application controls the absolute value of the temperature difference of each glass liquid after melting a plurality of glass compositions of different colors at a viscosity of 300P to be less than or equal to 30°C, and the absolute value of the temperature difference at a viscosity of 600P to be less than or equal to 40°C, thereby ensuring that the colored substrate glass can be formed intact without defects such as breakage, flaws, and cracks.
[0063] 3. The present invention controls the forming of a plurality of glass compositions of different colors and performs heat treatment, and the absolute value of the difference between the average thermal expansion coefficients of the glass compositions of different colors is less than or equal to 0.8×10 -6 / K can achieve uniform strengthening of colored microcrystalline glass, which has good strength performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 This is the molding diagram of the microcrystalline glass prepared in Example 4.
[0065] Figure 2 This is the forming diagram of the microcrystalline glass prepared in Comparative Example 2.
[0066] Figure 3 This is the DSC curve diagram of Example 2.
[0067] Figure 4 This is the DSC curve diagram of Comparative Example 4.
[0068] Figure 5This is the XRD pattern of the S11 component.
[0069] Figure 6 This is the viscosity-temperature curve of Example 1.
[0070] Figure 7 This is the viscosity-temperature curve of Comparative Example 1. DETAILED DESCRIPTION
[0071] This application will combine the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on this application belong to the scope of protection of this application.
[0072] Unless otherwise specified in specific circumstances in this application, the numerical ranges listed herein include upper and lower limits, as well as all integers and fractions within the range, and are not limited to the specific values listed when the range is limited. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0073] In the first aspect, the present application provides a colored microcrystalline glass, which is obtained by ceramicizing a colored substrate glass; the colored substrate glass comprises a plurality of glass compositions of different colors melted into a plurality of glass liquids of different colors and then integrally molded, and the colored substrate glass has different color regions. The "molded into one" mentioned in the present application should be understood as that the glass compositions of different colors are melted into glass liquids separately and will not mix with each other, but that during molding, the glass liquids of different colors are only bonded with their edges intact and then molded into a whole.
[0074] In some embodiments, the number of glass compositions of different colors is 2 or more, or 3 or more.
[0075] In some embodiments, the glass compositions of various colors include the following components, measured in mole percentage of oxides:
[0076] SiO 2 : 66~71%;
[0077] Al 2 O 3 : 3.5~5.0%;
[0078] Na 2 O: 0-5.0%, not 0;
[0079] Li 2 O: 18-23%;
[0080] P2 O 5 : 0.5~1.5%;
[0081] ZrO 2 : 1.5~4.0%;
[0082] At least one colorant, the colorant is Au, Ag, Cr 2 O 3 , transition metal oxides, and at least one of rare earth metal oxides.
[0083] In some embodiments, the colorant is used in an amount less than or equal to 3.00 mol %.
[0084] In some embodiments, the glass compositions of various colors further include the following components, measured in mole percentage of oxides:
[0085] K 2 O: 0~0.5%;
[0086] CaO: 0-1.5%;
[0087] B 2 O 3 :0~2%.
[0088] SiO 2 It is an oxide that forms a glass network skeleton and can be used to stabilize the network structure of glass and glass-ceramics. 2 The content of SiO is 66.00 mol% to 71.00 mol%, and more preferably 66.00 mol% to 70.00 mol%. For example, SiO 2 The content of can be 66.00mol%, 66.50mol%, 67.06mol%, 67.30mol%, 67.45mol%, 67.62mol%, 67.74mol%, 67.76mol%, 68.18mol%, 68.24mol%, 68.36mol%, 68.46mol%, 68.61mol%, 68.89mol%, 69.00mol%, 69.15mol%, 69.25mol%, 69.50mol%, 69.72mol%, 69.92mol%, 69.98mol%, 70.29mol%, 70.50mol%, 71.00mol%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0089] Al 2 O 3It can also stabilize the network and improve the strength of the glass structure, and improve the scratch resistance and drop resistance of the glass. 2 O 3 The content is 3.50mol% to 5.00mol%, for example, Al 2 O 3 The content of can be 3.50mol%, 3.75mol%, 3.95mol%, 3.97mol%, 3.98mol%, 3.99mol%, 4.01mol%, 4.02mol%, 4.04mol%, 4.07mol%, 4.11mol%, 4.18mol%, 4.19mol%, 4.20mol%, 4.21mol%, 4.26mol%, 4.27mol%, 4.50mol%, 4.75mol%, 4.86mol%, 4.90mol%, 5.00mol%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0090] In some embodiments, Na 2 The content of O is within 5.00 mol% and not 0. For example, Na 2 The content of O can be 0.28 mol%, 0.29 mol%, 0.31 mol%, 1.00 mol%, 1.41 mol%, 1.42 mol%, 1.43 mol%, 1.44 mol%, 1.45 mol%, 1.47 mol%, 1.64 mol%, 1.67 mol%, 3.02 mol%, 3.10 mol%, 3.12 mol%, 3.15 mol%, 4.20 mol%, 4.67 mol%, 5.00 mol%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0091] Li 2 O is lithium necessary to form a lithium silicate crystalline phase when the substrate glass is ceramized to form a glass-ceramic. 2 The content of O is 18.00 mol% to 23.00 mol%. For example, Li 2The content of O can be 18.00mol%, 18.58mol%, 18.74mol%, 19.12mol%, 19.50mol%, 20.61mol%, 20.66mol%, 20.67mol%, 20.74mol%, 20.76mol%, 20.80mol%, 20.81mol%, 20.96mol%, 20.99mol%, 21.06mol%, 21.09mol%, 21.13mol%, 21.28mol%, 21.49mol%, 21.84mol%, 22.01mol%, 22.60mol%, 22.72mol%, 22.77mol%, 23.00mol%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0092] In some embodiments, K 2 The content of O is 0 mol% to 0.50 mol%. For example, K 2 The content of O can be 0 mol%, 0.01 mol%, 0.08 mol%, 0.09 mol%, 0.12 mol%, 0.15 mol%, 0.30 mol%, 0.40 mol%, 0.50 mol%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0093] P 2 O 5 Can be used as a nucleating agent to form bulk nucleation. In some embodiments, P 2 O 5 The content of P is 0.50 mol% to 1.50 mol%, for example, 2 O 5 The content of can be 0.50mol%, 0.67mol%, 0.72mol%, 0.80mol%, 0.82mol%, 0.83mol%, 0.84mol%, 0.85mol%, 0.95mol%, 0.98mol%, 0.99mol%, 1.00mol%, 1.03mol%, 1.06mol%, 1.08mol%, 1.21mol%, 1.50mol%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0094] ZrO 2 Generally present in glass systems as a nucleating agent. In some embodiments, ZrO 2The content of ZrO is 1.50 mol% to 4.00 mol%. For example, ZrO 2 The content of can be 1.50mol%, 1.62mol%, 1.68mol%, 1.70mol%, 1.72mol%, 1.74mol%, 1.85mol%, 2.50mol%, 2.54mol%, 2.58mol%, 2.59mol%, 2.62mol%, 2.66mol%, 2.67mol%, 3.10mol%, 3.25mol%, 3.46mol%, 3.67mol%, 3.77mol%, 4.00mol%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0095] CaO can increase the chemical stability and mechanical strength of the glass. In some embodiments, the content of CaO is 0 to 1.5 mol%, for example, the content of CaO can be 0, 0.10 mol%, 0.20 mol%, 0.53 mol%, 0.75 mol%, 0.77 mol%, 0.78 mol%, 0.79 mol%, 0.85 mol%, 0.86 mol%, 0.89 mol%, 0.97 mol%, 1.00 mol%, 1.34 mol%, 1.49 mol%, 1.50 mol%, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.
[0096] B 2 O 3 Helps to reduce the melting temperature of the substrate glass. In some embodiments, B 2 O 3 The content of B is 0 to 2.00 mol%. 2 O 3 The content of can be 0, 0.29mol%, 0.30mol%, 0.31mol%, 0.62mol%, 1.20mol%, 1.42mol%, 1.49mol%, 1.51mol%, 1.52mol%, 1.54mol%, 1.80mol%, 1.87mol%, 2.00mol%, etc., and all ranges and sub-ranges between the above values. It should be understood that in an embodiment, any of the above ranges can be combined with any other ranges.
[0097] In some embodiments, the colorant includes Au, Ag, Cr 2 O 3, transition metal oxides, and rare earth metal oxides. The colorant is a common coloring substance in the art, such as Au, Ag, Cr 2 O 3 , transition metal oxides, rare earth metal oxides, etc. The colorant can be Fe 2 O 3 , Er 2 O 3 、NiO、MnO 2 Cr 2 O 3 、CoO、Ho 2 O 3 、Nd 2 O 3 , Cu 2 O, and may not be limited to the above colorants. Similarly, the colors presented by the colored glass-ceramics of the present application include but are not limited to red, pink, yellow, green, blue, purple and black. The colorant can be used alone or in combination. For example, when used alone, Fe 2 O 3 Make the glass appear black or smoky gray, 2 O 3 Makes the glass pink, NiO makes the glass brown or green, MnO 2 Makes the glass appear reddish brown, Cr 2 O 3 Makes the glass green, CoO makes the glass blue, Ho 2 O 3 Makes the glass appear yellow, Nd 2 O 3 Makes the glass appear purple-red, Cu 2 O makes the glass appear sky blue. When used in combination, Fe 2 O 3 Can be used with MnO 2 , NiO, and MnO 2 、NiO、Cr 2 O 3 Four kinds of mixed use; Fe 2 O 3 and MnO 2 or Cr 2 O 3Or NiO mixed use, can deepen the coloring degree of substrate glass, microcrystalline glass or microcrystalline glass products. In some embodiments, the amount of colorant is less than or equal to 3.00mol%. In some embodiments, the amount of colorant can be 0, 0.01mol%, 0.02mol%, 0.05mol%, 0.20mol%, 0.30mol%, 0.48mol%, 0.49mol%, 0.51mol%, 0.65mol%, 0.97mol%, 1.50mol%, 1.80mol%, 2.00mol%, 2.10mol%, 2.30mol%, 2.50mol%, 2.70mol%, 2.90mol%, 3.00mol%, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.
[0098] In some embodiments, the glass compositions of different colors are 2 or more, or 3 or more. In some embodiments, the glass compositions of different colors have components other than colorants and their contents that are partially or completely different.
[0099] Considering that defects such as breakage, flaws, and cracks will not occur during the overall molding of the glass composition of various colors to prepare the colored substrate glass, the glass composition of various colors of the present application is melted into glass liquid of various colors and then molded to characterize the properties of the substrate glass by the temperature when the viscosity is 300P and the temperature when the viscosity is 600P on the viscosity-temperature curve. In some embodiments, when the glass composition of various colors is melted into glass liquid of various colors, the following conditions are met during molding: the absolute value of the temperature difference between the glass liquids of various colors at a viscosity of 300P is less than or equal to 30°C, and the absolute value of the temperature difference at a viscosity of 600P is less than or equal to 40°C. Preferably, the absolute value of the temperature difference between the glass liquids of various colors at a viscosity of 300P can be less than or equal to 30°C, less than or equal to 28°C, less than or equal to 25°C, less than or equal to 23°C, less than or equal to 20°C, less than or equal to 18°C, less than or equal to 15°C, less than or equal to 10°C, less than or equal to 5°C, less than or equal to 3°C, less than or equal to 1°C, etc., and all ranges and sub-ranges between the above values. Further preferably, the absolute value of the temperature difference between the glass liquids of various colors at a viscosity of 600P is less than or equal to 40°C, less than or equal to 30°C, less than or equal to 20°C, less than or equal to 10°C, less than or equal to 8°C, less than or equal to 5°C, less than or equal to 3°C, less than or equal to 1°C, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.
[0100] In the present application, there is no fixed requirement for the molding method of the colored substrate glass, as long as the purpose of the present application can be achieved. In some embodiments, the molding method of the colored substrate glass can be at least one of casting molding, calendering molding, overflow molding, float molding, and narrow slit drawdown. Preferably, the molding method of the colored substrate glass is casting molding.
[0101] In some embodiments, the glass liquids of different colors are molded into one piece in different regions during casting, specifically, they are molded into one piece in different regions of the same mold, and the molding conditions of the glass liquids of different colors are exactly the same during this molding process.
[0102] In some embodiments, the main crystalline phase of the glass compositions of different colors after each forming and heat treatment is the same.
[0103] In some embodiments, the main crystalline phase of the glass compositions of different colors after each forming and heat treatment includes a lithium-containing crystalline phase, as long as it is a lithium-containing crystalline phase that can be formed in the art, specifically, it can be at least one of petalite, lithium monosilicate, lithium disilicate, eucryptite, etc.
[0104] In some embodiments, when the glass compositions of different colors are formed and heat-treated, the absolute value of the temperature difference between the nucleation temperatures of the glass compositions of different colors is less than or equal to 20°C. In some embodiments, when the glass compositions of different colors are formed and heat-treated, the absolute value of the temperature difference between the nucleation temperatures of the glass compositions of different colors is less than or equal to 18°C, less than or equal to 15°C, less than or equal to 13°C, less than or equal to 11°C, less than or equal to 9°C, less than or equal to 7°C, less than or equal to 5°C, less than or equal to 3°C, less than or equal to 1°C, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges.
[0105] In some embodiments, when the glass compositions of different colors are heat-treated after being formed, the absolute value of the temperature difference between the crystallization temperatures of the glass compositions of different colors is less than or equal to 20°C. In some embodiments, when the glass compositions of different colors are heat-treated after being formed, the absolute value of the temperature difference between the crystallization temperatures of the glass compositions of different colors is less than or equal to 18°C, less than or equal to 15°C, less than or equal to 13°C, less than or equal to 11°C, less than or equal to 9°C, less than or equal to 7°C, less than or equal to 5°C, less than or equal to 3°C, less than or equal to 1°C, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges.
[0106] In some embodiments, after the glass compositions of different colors are formed and heat treated, the absolute value of the difference between the average thermal expansion coefficients of the glass compositions of different colors is less than or equal to 0.8×10 -6 In some embodiments, after the glass compositions of different colors are formed and heat treated, the absolute value of the difference between the average thermal expansion coefficients of the glass compositions of different colors is less than or equal to 0.6×10 -6 / K, less than or equal to 0.5×10 -6 / K, less than or equal to 0.4×10 -6 / K, less than or equal to 0.3×10 -6 / K, less than or equal to 0.1×10 -6 / K, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0107] In some embodiments, the colored substrate glass is subjected to heat treatment to prepare colored microcrystalline glass, and the heat treatment includes nucleation treatment and crystallization treatment. In some embodiments, the temperature of the nucleation treatment is 500-600°C, and the time of the nucleation treatment is 180-300min. In some embodiments, the temperature of the nucleation treatment can be 500°C, 520°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, etc., and all ranges and sub-ranges between the above values. In some embodiments, the time of the nucleation treatment can be 180min, 200min, 220min, 240min, 260min, 280min, 300min, etc., and all ranges and sub-ranges between the above values. In some embodiments, the temperature of the crystallization treatment is 600-800°C, and the time of the crystallization treatment is 30-180min. In some embodiments, the temperature of the crystallization treatment may be 600°C, 620°C, 640°C, 650°C, 660°C, 670°C, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, etc., and all ranges and sub-ranges between the above values. In some embodiments, the time of the crystallization treatment may be 30 min, 50 min, 60 min, 80 min, 90 min, 100 min, 120 min, 140 min, 160 min, 180 min, etc., and all ranges and sub-ranges between the above values.
[0108] In some embodiments, the nucleation treatment is to heat the colored substrate glass from room temperature to the nucleation temperature at a heating rate of 1 to 10°C / min. In some embodiments, the heating rate of the nucleation treatment can be 1°C / min, 3°C / min, 5°C / min, 7°C / min, 9°C / min, 10°C / min, etc., and all ranges and sub-ranges between the above values. In some embodiments, the crystallization treatment is to heat the colored substrate glass from the nucleation temperature to the crystallization temperature at a heating rate of 1 to 10°C / min. In some embodiments, the heating rate of the crystallization treatment can be 1°C / min, 3°C / min, 5°C / min, 7°C / min, 9°C / min, 10°C / min, etc., and all ranges and sub-ranges between the above values. It should be understood that in the implementation scheme, any of the above ranges can be combined with any other ranges.
[0109] In a second aspect, the present application provides a method for preparing the above-mentioned colored micro-ceramic glass, comprising the following steps:
[0110] Step 1: Mix components of glass compositions of various colors respectively, and then melt them to obtain glass liquids of various colors;
[0111] Step 2: forming the glass liquids of various colors obtained in step 1 into one body, and subjecting them to annealing treatment to obtain colored substrate glass with different color regions;
[0112] Step 3: Heat-treat the colored substrate glass obtained in step 2 to obtain colored microcrystalline glass.
[0113] In some embodiments, in step 1, the melting temperature is 1350-1650°C, and the melting time is 4-13h. In some embodiments, in step 1, the melting temperature can be 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C, 1650°C, etc., and all ranges and sub-ranges between the above values. In some embodiments, in step 1, the melting time is 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0114] In some embodiments, in step 2, the glass liquids of different colors are molded into one piece in different regions. Specifically, the glass liquids of different colors are molded into one piece in different regions of the same mold, and the molding conditions of the glass liquids of different colors are exactly the same during this molding process.
[0115] In some embodiments, in step 2, the molding method can be at least one of casting molding, calendaring molding, overflow molding, float molding, and narrow slit draw-down. Preferably, in step 2, the molding method is casting molding.
[0116] In some embodiments, in step 2, the annealing temperature is 450-500°C, and the annealing time is 12-48h. In some embodiments, in step 2, the annealing temperature can be 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, etc., and all ranges and sub-ranges between the above values. In some embodiments, in step 2, the annealing time can be 12h, 14h, 16h, 18h, 20h, 23h, 25h, 27h, 29h, 32h, 35h, 38h, 40h, 42h, 44h, 46h, 48h, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.
[0117] In some embodiments, in step 3, the heat treatment includes a nucleation treatment and a crystallization treatment. In some embodiments, the temperature of the nucleation treatment is 500-600°C, and the holding time of the nucleation treatment is 180-300min. In some embodiments, the temperature of the nucleation treatment can be 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, etc., and all ranges and sub-ranges between the above values. In some embodiments, the holding time of the nucleation treatment can be 180min, 200min, 220min, 240min, 260min, 280min, 300min, etc., and all ranges and sub-ranges between the above values. In some embodiments, the temperature of the crystallization treatment is 600-800°C, and the holding time of the crystallization treatment is 30-180min. In some embodiments, the temperature of the crystallization treatment may be 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, 730°C, 750°C, 770°C, 790°C, 800°C, etc., and all ranges and sub-ranges between the above values. In some embodiments, the holding time of the crystallization treatment may be 30min, 50min, 70min, 90min, 100min, 120min, 140min, 160min, 180min, etc., and all ranges and sub-ranges between the above values. In some embodiments, the colored substrate glass is heated from room temperature to the temperature of the nucleation treatment at a heating rate of 3 to 10°C / min. In some embodiments, the colored substrate glass is heated from the temperature of the nucleation treatment to the temperature of the crystallization treatment at a heating rate of 3 to 10°C / min. In some embodiments, whether it is the temperature of the nucleation treatment or the temperature of the crystallization treatment, the heating rate can be 3°C / min, 5°C / min, 7°C / min, 9°C / min, 10°C / min, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0118] In some embodiments, in step 3, when the glass compositions of different colors are heat-treated after being formed, the absolute value of the temperature difference between the nucleation temperatures of the glass compositions of different colors is less than or equal to 20°C. In some embodiments, in step 3, when the glass compositions of different colors are heat-treated after being formed, the absolute value of the temperature difference between the nucleation temperatures of the glass compositions of different colors is less than or equal to 18°C, less than or equal to 15°C, less than or equal to 13°C, less than or equal to 11°C, less than or equal to 9°C, less than or equal to 7°C, less than or equal to 5°C, less than or equal to 3°C, less than or equal to 1°C, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges.
[0119] In some embodiments, in step 3, when the glass compositions of different colors are heat-treated after being formed, the absolute value of the temperature difference between the crystallization temperatures of the glass compositions of different colors is less than or equal to 20°C. In some embodiments, in step 3, when the glass compositions of different colors are heat-treated after being formed, the absolute value of the temperature difference between the crystallization temperatures of the glass compositions of different colors is less than or equal to 18°C, less than or equal to 15°C, less than or equal to 13°C, less than or equal to 11°C, less than or equal to 9°C, less than or equal to 7°C, less than or equal to 5°C, less than or equal to 3°C, less than or equal to 1°C, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges.
[0120] In some embodiments, in step 3, after the glass compositions of different colors are formed and heat treated, the absolute value of the difference between the average thermal expansion coefficients of the glass compositions of different colors is less than or equal to 0.8×10 -6 In some embodiments, the absolute value of the difference between the average thermal expansion coefficients of the substrate glass in different color regions during the heat treatment of the colored substrate glass is less than or equal to 0.6×10 -6 / K, less than or equal to 0.5×10 -6 / K, less than or equal to 0.4×10 -6 / K, less than or equal to 0.3×10 -6 / K, less than or equal to 0.1×10 -6 / K, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.
[0121] In a third aspect, the present application provides a strengthened colored microcrystalline glass, which is obtained by chemically strengthening the colored microcrystalline glass as described above or the colored microcrystalline glass prepared by the above-mentioned method for preparing the colored microcrystalline glass.
[0122] In some embodiments, chemical strengthening comprises single-step chemical strengthening or multi-step chemical strengthening. In some embodiments, single-step chemical strengthening uses a mixture containing NaNO 3 A salt bath, preferably NaNO 3The content is 30-100wt%. In some embodiments, the temperature of single-step chemical strengthening is 450-500°C. In some embodiments, the temperature of single-step chemical strengthening can be 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, etc., and all ranges and sub-ranges between the above values. In some embodiments, the time of single-step chemical strengthening is 1-15h. In some embodiments, the time of single-step chemical strengthening is 1h, 3h, 5h, 7h, 9h, 10h, 12h, 13h, 14h, 15h, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.
[0123] In some embodiments, the multi-step chemical strengthening includes two steps of chemical strengthening, wherein the first step of chemical strengthening uses a 3 A salt bath, preferably NaNO 3 The content of KNO is 30-100wt%; the second step of chemical strengthening uses 3 A salt bath, preferably KNO 3 The content is 60-100wt%. In some embodiments, the temperature of the first step of chemical strengthening is 450-500°C, and the time of the first step of chemical strengthening is 2-10h. In some embodiments, the temperature of the first step of chemical strengthening can be 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, etc., and all ranges and sub-ranges between the above values. In some embodiments, the time of the first step of chemical strengthening can be 2h, 4h, 6h, 8h, 10h, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.
[0124] In some embodiments, the temperature of the second step chemical strengthening is 450-500°C, and the time of the second step chemical strengthening is 1-5h. In some embodiments, the temperature of the second step chemical strengthening can be 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, etc., and all ranges and sub-ranges between the above values. In some embodiments, the time of the second step chemical strengthening can be 1h, 2h, 3h, 4h, 5h, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.
[0125] In some embodiments, at a thickness of 0.60 mm, the average single rod static compressive strength of the strengthened colored glass-ceramics is greater than or equal to 300 N, preferably 320-450 N. In some embodiments, at a thickness of 0.60 mm, the average single rod static compressive strength of the strengthened colored glass-ceramics may be 300-450 N, 300-430 N, 300-410 N, or 310-400 N, and may also be 300 N, 330 N, 350 N, 380 N, 390 N, or 400 N, and all ranges and sub-ranges between the above values. It should be understood that in the embodiments, any of the above ranges may be combined with any other ranges.
[0126] In some embodiments, the average drop resistance height of the strengthened colored glass-ceramics is greater than or equal to 1.8m, preferably 1.80-2.5m. In some embodiments, at a thickness of 0.60mm, the average drop resistance height of the strengthened colored glass-ceramics can be 1.82-2.5m, 1.85-2.5m, 1.90-2.3m or 1.92-2.2m, and can also be 1.80m, 1.82m, 1.85m, 1.87m, 1.89m, 1.90m, 1.93m, 1.95m, 1.98m, 2.0m, 2.2m, 2.3m or 2.5m, and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.
[0127] In a fourth aspect, the present application provides an application of the colored microcrystalline glass as described above, or the colored microcrystalline glass prepared by the above-mentioned colored microcrystalline glass preparation method, or the above-mentioned strengthened colored microcrystalline glass in mobile phone back covers, electronic terminals, decorative parts, handicrafts, jewelry or portable digital devices.
[0128] In a fifth aspect, a consumer electronic product comprises: a housing comprising a front surface, a back surface and a side surface; electronic components at least partially located within the housing, the electronic components comprising at least a controller, a memory and a display, the display being located at the front surface of the housing or adjacent to the front surface of the housing; and a cover glass arranged on the display, wherein at least a portion of the housing comprises the colored microcrystalline glass as described above, or the colored microcrystalline glass prepared by the method for preparing the colored microcrystalline glass as described above, or the strengthened colored microcrystalline glass as described above.
[0129] In a sixth aspect, an electronic device comprises the colored microcrystalline glass as described above, or the colored microcrystalline glass prepared by the method for preparing the colored microcrystalline glass as described above, or the strengthened colored microcrystalline glass as described above.
[0130] In the seventh aspect, test method, the relevant measurement methods involved in this application are explained as follows.
[0131] Thermal analysis (DSC) test:
[0132] The instrument used was a Mettler-Toledo TGA / DSC 3+ simultaneous thermal analyzer. The test was carried out in accordance with JY / T 0589.5-202. The standard substance used in the test was α-Al 2 O 3 The sample container is a platinum crucible, the instrument is placed in an ambient temperature of 24°C and an air humidity of 40%. The glass is ground and sieved through 200 mesh to obtain the sample to be tested. About 20 mg of the sample is weighed and heated from room temperature to 900°C at a heating rate of 10°C / min under a nitrogen atmosphere to obtain the DSC curve of the sample.
[0133] Viscosity-temperature test:
[0134] The test was carried out in accordance with ASTM C965-96 (Reapproved 2017), and the test instrument was a combination of an American Orton RSV-1700 and an American Brookfield DV2TLV viscometer.
[0135] Average thermal expansion coefficient test:
[0136] Thermal expansion coefficient (α 20℃-300℃ ) The test was carried out in accordance with the test method of GB / T7962.16-2010; the test instrument was the German Lindsay vertical mode thermal expansion instrument (L75VD 1000).
[0137] XRD test:
[0138] The glass-ceramic sample is ground into glass fine powder with a grinding machine, and its particle size is less than 75 μm, and then it is tested by an X-ray diffractometer (Shimadzu's XRD-6100) to obtain an XRD diffraction peak curve. The X-ray diffractometer used in the present invention is Shimadzu's XRD-6100, the target material is copper, the test incident angle range is 2θ=10-80°, the scanning speed is 0.02-6° / min, the working voltage is 40 kV, and the working current is 30 mA.
[0139] Test method for crystal content:
[0140] Import the X-ray diffractometer test result file (RAW format) into the X-ray diffraction data Rietveld refinement software (such as Gsas, Fullprof, Maud), perform fitting and calculation, and you can get the crystal content / crystallinity in the microcrystalline glass sample. The ratio of the fitted crystal phase peak area to the fitted total peak area is the crystal content, which is also referred to as crystallinity in this application.
[0141] Glass thickness:
[0142] Determined by laser thickness gauge test. The thickness change of glass-ceramics before and after chemical strengthening is very small and can be ignored.
[0143] Vickers hardness test:
[0144] The test was carried out in accordance with the standard "GB / T 37900-2019 Ultra-thin glass hardness and fracture toughness test method - small load Vickers hardness indentation method".
[0145] Single rod static pressure strength test:
[0146] Place the glass sample to be tested on the bottom ring of the tensile testing machine (LT-850A), start the test software, and set the moving speed of the extrusion rod (rod diameter 8mm, indenter arc radius 10mm) to 50mm / min. Click to start the test, and the extrusion rod will apply force to the center of the glass sample to be tested at the set moving speed until the glass sample cracks and breaks.
[0147] The test software will automatically read the force (N) when the glass sample breaks as the test result.
[0148] Take 10 glass samples under the same conditions for testing, and take the average value of the test results as the average single-rod static pressure strength of the glass samples to be tested.
[0149] Average drop height test:
[0150] Average drop height: The average value obtained by dividing the sum of the drop heights measured for multiple glass samples by the number of samples measured is used to characterize the glass's resistance to cracking on the contact surface.
[0151] Take at least 10 glass samples from each batch for testing, and take the average drop resistance height of all glass samples. The formula is as follows:
[0152] Wherein, n is the number of glass samples tested in each batch, and hi is the drop resistance height tested for a single glass sample.
[0153] Among them, the test method for the drop resistance of glass samples is:
[0154] Step 1: Stick the glass sample to be tested with a length, width and thickness of 50mm×50mm×0.7mm on the front of the 187g model machine;
[0155] Step 2: Place the model machine on the Green Figure LT-SKDL-CD drop machine, with the glass sample facing the sandpaper, and drop it from a certain drop height to impact the 80-grit sandpaper located directly below the model machine, simulating the normal drop posture of a mobile phone.
[0156] If the glass sample does not break, the drop height of the model machine is increased in a certain pattern. For example, the drop height starts from 0.4m, and the sample is dropped once. If it does not break, the drop height is increased by 0.1m each time until the glass sample breaks.
[0157] Step 3: Record the last drop height of the glass sample when it breaks as the anti-drop height. For example, if the drop height when it breaks is 0.5m, the anti-drop height of the sample is 0.4m.
[0158] In the eighth aspect, the present application is described below through specific embodiments.
[0159] Example 1
[0160] Step 1: Prepare the raw materials of the glass compositions S2 and S4 in Table 1 respectively, and then mix them in a V-type mixer for 30 minutes to obtain the S2 mixture and the S4 mixture respectively, and then transfer the two mixtures to different platinum-rhodium crucibles, and melt them in a lifting furnace to obtain two glass liquids of different colors; the melting temperature is 1550° C., and the melting time is 5 hours;
[0161] Step 2: Cool the two different colored glass liquids obtained in step 1 to an appropriate temperature, and then pour them into the mold from both sides to form them into one piece; after cooling to 800°C, put them into an annealing furnace and anneal them at 500°C for 13 hours; then cool them to room temperature with the furnace to obtain colored substrate glass with different color areas;
[0162] Step 3: heat-treating the colored substrate glass obtained in step 2 to obtain colored micro-ceramics;
[0163] The heat treatment includes nucleation treatment and crystallization treatment; the temperature and time of the nucleation treatment and crystallization treatment are shown in Table 4 below.
[0164] The colored microcrystalline glass obtained above is shaped, cut and ground to obtain colored microcrystalline glass sheets of required specifications, such as 50mm×50mm×0.7mm (specification dimensions) in length, width and thickness, and relevant performance tests are carried out.
[0165] The 50 mm × 50 mm × 0.7 mm colored microcrystalline glass slices obtained above were polished and then immersed in a salt bath for chemical strengthening to obtain strengthened colored microcrystalline glass; the composition of the salt bath and the strengthening process conditions are shown in Table 7 below.
[0166] Examples 2-6 were prepared under the same operating conditions as Example 1, except that the glass compositions used to prepare the colored glass-ceramics were different as shown in Tables 1-3 and the molding and heat treatment processes were different as shown in Table 4. The performance parameters of the colored glass-ceramics of Examples 1-6 are shown in Table 4, and the performance parameters of the strengthened colored glass-ceramics prepared using the colored glass-ceramics of Examples 1-6 are shown in Table 7.
[0167] Comparative Examples 1-4 were also prepared under the same operating conditions as Example 1, except that the glass compositions for preparing colored glass-ceramics were different as shown in Tables 1-3, and the molding and heat treatment processes were different as shown in Table 6. Comparative Example 1-2 failed to achieve complete overall molding, and thus failed to prepare complete colored glass-ceramics; although Comparative Example 4 was able to be molded into one piece, it also failed to prepare complete colored glass-ceramics.
[0168] In addition, Example 7
[0169] Step 1: Prepare the raw materials of each component of glass composition S20, S21 and S22 in Table 3 respectively, and then mix them in a V-type mixer for 30 minutes to obtain S20 mixture, S21 mixture and S22 mixture respectively, and then transfer the three mixtures to different platinum-rhodium crucibles respectively, and melt them in a lifting furnace to obtain three glass liquids of different colors; the melting temperature is 1550° C., and the melting time is 5 hours;
[0170] Step 2: Cool the three different colored glass liquids obtained in step 1 to an appropriate temperature, and then pour them into the mold from different positions of the mold to form them into one piece; after cooling to 800°C, put them into an annealing furnace and anneal them at 500°C for 13 hours; then cool them to room temperature with the furnace to obtain colored substrate glass with different color areas;
[0171] Step 3: heat-treat the colored substrate glass obtained in step 2 to obtain colored microcrystalline glass; the heat treatment includes nucleation treatment and crystallization treatment; the temperature and time of the nucleation treatment and crystallization treatment are shown in Table 5 below.
[0172] The colored microcrystalline glass obtained above is shaped, cut and ground to obtain colored microcrystalline glass sheets of required specifications, such as 50mm×50mm×0.7mm (specification dimensions) in length, width and thickness, and relevant performance tests are carried out.
[0173] The 50 mm × 50 mm × 0.7 mm colored microcrystalline glass slices obtained above were polished and then immersed in a salt bath for chemical strengthening to obtain strengthened colored microcrystalline glass; the composition of the salt bath and the strengthening process conditions are shown in Table 8 below.
[0174] Comparative Example 5
[0175] The glass composition S23 and the glass composition S19 in Table 3 are used to prepare colored microcrystalline glass. The glass composition S23 is used to prepare a main crystal phase of ZnAl 2 O 4 and MgAl 2 O 4 Although the viscosity-temperature difference between glass composition S23 and glass composition S19 can meet the requirements, the nucleation and crystallization temperatures are very different, and uniform crystallization cannot be performed as a whole, so colored glass-ceramics cannot be prepared.
[0176] Table 1. Glass composition and its own heat treatment process and related performance parameters
[0177]
[0178]
[0179] Table 2. Glass composition and its own heat treatment process and related performance parameters
[0180]
[0181]
[0182] Table 3. Glass composition and its own heat treatment process and related performance parameters
[0183]
[0184]
[0185] Table 4. Forming and ceramicizing process conditions and performance parameters of colored microcrystalline glass of Examples 1-6
[0186]
[0187] Table 5. Forming and ceramicization process conditions and performance parameters of the colored microcrystalline glass of Example 7
[0188]
[0189] Table 6. Forming and ceramicization process conditions and performance parameters of colored microcrystalline glass of comparative examples 1-5
[0190]
[0191] Table 7. Composition, strengthening process conditions and performance parameters of the salt bath for strengthening colored glass-ceramics of Examples 1-6
[0192]
[0193]
[0194] Table 8. Composition, strengthening process conditions and performance parameters of the salt bath for strengthening the colored microcrystalline glass of Example 7
[0195]
[0196] Table 9. Composition, strengthening process conditions and performance parameters of the salt bath of the strengthened colored microcrystalline glass of Comparative Example 3
[0197] Composition (mol%) Comparative Example 3 Chemically enhanced salt bath <![CDATA[69.97wt%KNO 3 +30wt%NaNO 3 +0.03wt%LiNO 3 ]]> Chemical strengthening temperature (℃) 470 Chemical strengthening temperature (℃) 6 Average single rod static pressure strength (N) 137 Average drop resistance height (m) 0.86
[0198] From the above table and attached figures, we can see that:
[0199] (1) Two or more components in the embodiment must satisfy the requirement that the temperature difference is less than 30°C when the viscosity is 300P and the temperature difference is less than 40°C when the viscosity is 600P, so that when preparing glass-ceramics with different colors in different regions in the embodiment, various colored glasses can be well formed in the mold. Figure 1 It can be seen that the joints between the two different color areas in the micro-ceramic glass have a very good molding effect, which is not much different from the surface of ordinary single-color micro-ceramic glass; Figure 3 It also shows that the two glass components of different colors in Example 2 have relatively close DSC curves, so that glasses of different color regions and different components can be formed under the same conditions. In addition, Tables 4 and 5 also prove that the microcrystalline glass prepared in the example has high strength and excellent strength performance.
[0200] (2) Two or more components in the embodiment must satisfy the requirement that the absolute value of the temperature difference between the nucleation temperatures is less than 20°C, and the absolute value of the temperature difference between the crystallization temperatures is less than 20°C, so as to ensure that the microcrystalline glass prepared in the embodiment can achieve uniform crystallization of various colored glasses in different regions, laying a foundation for subsequent chemical strengthening.
[0201] (3) The difference in thermal expansion coefficient between two or more formulations in the embodiment must be less than 0.8×10 -6 / K, so that the microcrystalline glass prepared in the embodiment can be uniformly strengthened during chemical strengthening, and the chemical strengthening process will not have an adverse effect on the original performance of the microcrystalline glass.
[0202] (4) Comparative Example 1 does not meet the condition that the temperature difference is less than 30°C when the viscosity is 300P, and Comparative Example 2 does not meet the condition that the temperature difference is less than 30°C when the viscosity is 300P and the temperature difference is less than 40°C when the viscosity is 600P, which leads to problems in the microcrystalline glass of these comparative examples from the very beginning of molding. Some comparative examples have cracks at the joints during the molding process.
[0203] Breakage makes it impossible to form a variety of colored glass in the mold; Figure 2 This is demonstrated in the exhibit where the viscosity difference between the different color regions at the molding temperature is too large to allow for a tight connection, resulting in fractures near the structure.
[0204] (5) Although Comparative Example 3 meets the requirements of viscosity, nucleation temperature and crystallization temperature, it does not meet the requirements of the present application for the difference in thermal expansion coefficient. As a result, although Comparative Example 3 can be formed when preparing microcrystalline glass of different color regions, after chemical strengthening, the microcrystalline glass of different color regions has inconsistent strengthened dimensional expansion, and the surface stress of the microcrystalline glass after strengthening is uneven, which ultimately deteriorates the performance of the microcrystalline glass.
[0205] (6) Although Comparative Example 4 meets the condition that the temperature difference when the viscosity is 300P is less than 30°C and the temperature difference when the viscosity is 600P is less than 40°C, Comparative Example 4 does not meet the condition that the absolute value of the temperature difference between the crystallization temperatures is less than 20°C. Figure 4 It can be clearly seen that the temperature ranges for nucleation and crystallization of different color regions in Comparative Example 4 are very different, which leads to inconsistent heat treatment conditions theoretically required for different color regions in this comparative example. Ultimately, the degree of crystallization of different color regions under the same heat treatment conditions is quite different, showing very obvious differences in appearance. One color region is completely crystallized and becomes transparent, while the other color region is in a semi-crystallized state. This shows that it is difficult to achieve controllable molding of different color regions in Comparative Example 4 under the same conditions.
[0206] (7) Comparative Example 5 is a comparison of different crystal phases. Although Comparative Example 5 meets the viscosity requirements of the present application, it does not meet the conditions of the heat treatment process of the present application. If heat treatment is performed according to the ceramicization conditions of S23, S19 will be devitrified and no colored microcrystalline glass can be obtained.
[0207] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.
Claims
1. A colored microcrystalline glass, characterized in that: The colored microcrystalline glass is obtained by ceramicizing colored substrate glass; the colored substrate glass comprises glass compositions of various colors melted into glass liquids of various colors and simultaneously molded into one, and the colored substrate glass has different color regions.
2. The colored micro-ceramic glass according to claim 1, characterized in that: When glass compositions of various colors are melted into glass liquids of various colors, the following conditions are met during molding: the absolute value of the temperature difference between the glass liquids of various colors when the viscosity is 300P is less than or equal to 30°C, and the absolute value of the temperature difference when the viscosity is 600P is less than or equal to 40°C.
3. The colored micro-ceramic glass according to claim 1 or 2, characterized in that: After the glass compositions of different colors are formed and ceramicized, the absolute value of the difference between the average thermal expansion coefficients of the glass compositions of different colors is less than or equal to 0.8×10 -6 / K.
4. The colored micro-ceramic glass according to claim 1 or 2, characterized in that: Measured in mole percentage of oxides, glass compositions of various colors include the following components: SiO2: 66-71%; Al2O3: 3.5-5.0%; Na2O: 0-5.0%, not 0; Li2O: 18-23%; P2O5: 0.5~1.5%; ZrO2: 1.5-4.0%; At least one colorant, the colorant is at least one of Au, Ag, Cr2O3, transition metal oxides, and rare earth metal oxides.
5. The colored micro-ceramic glass according to claim 4, characterized in that: Measured in mole percentage of oxides, glass compositions of various colors also include the following components: K2O: 0~0.5%; CaO: 0-1.5%; B2O3: 0~2%.
6. The colored microcrystalline glass according to any one of claims 1 to 5, characterized in that: The glass compositions of the plurality of different colors are 2 or more, or 3 or more.
7. The colored microcrystalline glass according to any one of claims 1 to 5, characterized in that: The compositions of glass compositions of various colors differ partially or completely in components other than colorants and their contents.
8. The colored microcrystalline glass according to any one of claims 1 to 5, characterized in that: The color substrate glass is formed by at least one of casting, calendering, overflow, float, and narrow-slit drawdown.
9. The colored microcrystalline glass according to any one of claims 1 to 5, characterized in that: Glass liquids of various colors are molded into one in different areas.
10. The colored micro-ceramic glass according to any one of claims 1 to 5, characterized in that: The main crystal phase of the glass compositions of various colors after molding and heat treatment is the same.
11. The colored micro-ceramic glass according to claim 10, characterized in that: The main crystal phase of the glass compositions of various colors after being formed and heat-treated is a lithium-containing crystal phase, including at least one of petalite, lithium monosilicate, lithium disilicate, and eucryptite.
12. The colored microcrystalline glass according to any one of claims 1 to 5, characterized in that: When the glass compositions of different colors are heat-treated after being formed, the absolute value of the temperature difference between the nucleation temperatures of the glass compositions of different colors is less than or equal to 20°C.
13. The colored microcrystalline glass according to any one of claims 1 to 5, characterized in that: When the glass compositions of different colors are heat-treated after being formed, the absolute value of the temperature difference between the crystallization temperatures of the glass compositions of different colors is less than or equal to 20°C.
14. A method for preparing colored microcrystalline glass, characterized in that: The method of preparing the colored micro-ceramic glass according to any one of claims 1 to 13 comprises the following steps: Step 1: Mix components of glass compositions of various colors respectively, and then melt them to obtain glass liquids of various colors; Step 2: forming the glass liquids of various colors obtained in step 1 into one body, and annealing the formed glass liquids to obtain colored substrate glass; Step 3: Heat-treat the colored substrate glass obtained in step 2 to obtain colored microcrystalline glass.
15. The preparation method according to claim 14, characterized in that: In step 2, glass liquids of various colors are molded into one piece in different areas.
16. The preparation method according to claim 15, characterized in that: In step 2, the molding method is at least one of casting molding, calendering molding, overflow molding, float molding, and narrow slit draw-down.
17. A strengthened colored microcrystalline glass obtained by chemically strengthening the colored microcrystalline glass as described in any one of claims 1 to 13 or the colored microcrystalline glass prepared by the method for preparing colored microcrystalline glass as described in any one of claims 14 to 16.
18. The strengthened colored micro-ceramic glass according to claim 17, characterized in that: Chemical strengthening includes single-step chemical strengthening or multi-step chemical strengthening.
19. Use of the colored microcrystalline glass as described in any one of claims 1 to 13, or the colored microcrystalline glass prepared by the preparation method of the colored microcrystalline glass as described in any one of claims 14 to 16, or the colored strengthened microcrystalline glass as described in claim 17 in mobile phone back covers, electronic terminals, decorative parts, handicrafts, jewelry or portable digital devices.
20. A consumer electronic product comprising: a housing including a front surface, a back surface, and a side surface; an electronic assembly at least partially located within the housing, the electronic assembly including at least a controller, a memory, and a display, the display being located at or adjacent to the front surface of the housing; And a cover glass arranged on the display, wherein at least a portion of the outer shell comprises the colored microcrystalline glass as described in any one of claims 1 to 13 or the colored microcrystalline glass prepared by the method for preparing the colored microcrystalline glass as described in any one of claims 14 to 16, or the strengthened colored microcrystalline glass as described in claim 17.
21. An electronic device comprising the colored microcrystalline glass described in any one of claims 1 to 13, or the colored microcrystalline glass prepared by the method for preparing the colored microcrystalline glass described in any one of claims 14 to 16, or the strengthened colored microcrystalline glass described in claim 17.
Citation Information
Patent Citations
Colored microcrystalline glass as well as preparation method and application thereof
CN116199427A
Glass ceramic with excellent acid and alkali resistance as well as preparation method and application of glass ceramic
CN117466535A
Preparation method of flow liner crystallite glass
CN1807303A
Production of marble and / or colored patterned glass / glass-ceramic products comprises preparing two different colored glass melts, bringing the melts together, shaping, cooling and optionally making into a ceramic
DE102005022981A1
Production of glass product having color stripe
JP2000109326A